Analisis Aksiologi dalam Pengelolaan Sumber Daya Alam dan Implikasinya terhadap Keberlanjutan Lingkungan - Sabira Yuliandini; Muhammad Sarjan (Mataram University, 2026)
The ecological crisis triggered by the massive exploitation of natural resources reflects the absence of an adequate value foundation in natural resource management practices in Indonesia. This study aims to analyze the axiological framework as a philosophical instrument in examining the values underlying natural resource management, identify its implications for environmental sustainability, and formulate a relevant environmental axiology paradigm as an ethical foundation for sustainable natural resource management. The method employed is qualitative with a library research approach and content analysis technique applied to various relevant and up to date scientific literature sources. The findings indicate that natural resource management in Indonesia remains dominated by an anthropocentric-economistic value orientation of a pragmatic-exploitative nature, resulting in massive deforestation, biodiversity loss, ecosystem pollution, and socio-ecological inequality. Conversely, an ecologically sustainable value orientation grounded in local wisdom, the precautionary principle, and intergenerational equity has been proven to contribute significantly to ecosystem recovery. This study concludes that the paradigm of ecocentrism integrated with biocentrism constitutes the most relevant ethical foundation for sustainable natural resource management. Paradigmatic reform in natural resource regulation and policy that integrates the values of respect for nature, moral responsibility, and ecological solidarity stands as the primary recommendation of this research.